أثر المعيار الدولي IFRS15 في الحد من إدارة الأرباح في الشركات المساهمة السعودية: دراسة تطبيقية على شركة اتحاد الاتصالات "موبايلي" - ناهس، فاطمة خزام بطي; الحسن، فتح الرحمن الحسن منصور Al-Hasan, Fathulrahman Alhasan Mansour (مركز البحث وتطوير الموارد البشرية - رماح, 2024)
تهدف هذه الدراسة إلى التعرف على معيار IFRS15 "الإيراد من العقود مع العملاء" الذي بدأ تطبيقه عام 2018م، ومعرفة تأثير تطبيقه على الحد من ممارسات إدارة الأرباح من خلال البحث والاطلاع على نتائج الدراسات السابقة في هذا الموضوع، وثم تطبيق ذلك على أزمة شركة اتحاد اتصالات "موبايلي" عام 2014م؛ أي قبل بدء تطبيق المعيار. فاستخدم المنهج الوصفي التحليلي في الجانب النظري، وباستخدام نموذج جونز المعدل على القوائم المالية المعلنة لشركة موبايلي للأعوام 2009م- 2014م، ثبت وجود ممارسة لإدارة الأرباح في شركة موبايلي، وبقراءة وتحليل أسباب الأزمة عام 2014م من خلال القوائم المالية وتعديلاتها والإيضاحات المعلنة والملاحظات واللقاءات التلفزيونية، توصلت هذه الدراسة إلى وجود أثر لتطبيق معيار "IFRS15 "الإيراد من العقود مع العملاء" في الحد من ممارسة إدارة الأرباح، وتتفق نتيجة هذه الدراسة مع العديد من نتائج دراسات سابقة مطبقة على أسواق مالية عربية وأجنبية التي تؤكد وجود تأثير في تطبيق معيار IFRS15 على ممارسة إدارة الأرباح. This study aimed to determine the impact of IFRS15 ―Revenue from Contracts with Customers‖, applied in 2018, on limiting profit management practices by utilizing the analytical descriptive approach in studying and analyzing the previous studies in the field, besides, identifying the causes of the 2014 financial crisis of Etihad Etisalat "Mobily" before the implementation of IFRS15. The Modified Jones model was applied on Mobily's released financial statements for the years 2009-2014 and showed that there were profit management practices in Mobily. Consequently, by studying and analyzing the causes of the 2014 crisis through the financial statements and their amendments, the announced clarifications, observations, and television interviews, the study identified one cause of the crisis that is the timing of revenue recognition where several errors occurred in some accounting operations when recording revenue. The result is consistent with previous studies applied on Arab and foreign financial markets. They confirm the impact of the application of IFRS15 on the practice of earnings management through the presence of a unified model for the timing of revenue recognition.. The researcher recommends utilizing different methodologies in future researches, larger samples, and different sectors to test the impact of IFRS15 on earnings management to achieve reliable and generalizable results..
Keywords: المعايير الدولية -- الشركات المساهمة -- وسائل الاتصالات -- السعودية